This time it's different … but not really! The 2014 European Parliament elections in Ireland. Issue 2 (2nd April 2016) - Quinlan, Stephen; Okolikj, Martin
ABSTRACT: This report provides a review of the 2014 European Parliament (EP) elections in Ireland. Conventional wisdom suggests attitudes to the incumbent government or to the candidates on offer have shaped EP elections in Ireland, with sentiments about the EU having little potency. 2014 had the potential to be different: the EU had been especially prominent in Ireland over the past four years since the 2010 EU–IMF (International Monetary Fund) bailout. The introduction of spitzenkandidaten (The President of the Commission had previously been chosen by a consensus of European leaders in the European Council, followed by approval from the EP. But under the Lisbon Treaty, the European Council must take into account the results of the EP elections when selecting the Commission President which gave the EP the power to influence the next Commission President, also gave credence to the idea that the 2014 elections might involve a stronger European dimension. Using data from media sources, an exit poll, and the 2014 European Election Study, our objective is to establish how the campaign evolved and what influenced the 2014 result in Ireland. We find the 2014 European elections for the most part were 'second-order', with vote choice mainly influenced by attitudes to the Fine-Gael/Labour coalition. Candidate personality also mattered. However, EU issues gained little traction in the campaign and opinions on the EU had minimal impact on party choice. Our results show that domestic politics remain key to understanding EP elections in Ireland.